A corrosion inhibitor and alkaline electrolyte for aluminum-air battery and preparation method thereof
By using N-alpha-fluorene methoxycarbonyl-N-epsilon-tert-butoxycarbonyl-D-lysine (FDLH) as a corrosion inhibitor and a strong alkaline alkaline alkaline electrolyte, the problem of hydrogen evolution corrosion of aluminum anode is solved, the anode utilization rate and electrolyte stability are improved, and the discharge performance of aluminum air batteries is significantly improved.
Patent Information
- Application Number
- CN202411672906.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
AI Technical Summary
The anode of the aluminum air battery is prone to hydrogen evolution corrosion during the battery operation, resulting in low utilization rate of the anode and fast corrosion rate.
N-alpha-fluorene methoxycarbonyl-N-epsilon-tert-butoxycarbonyl-D-lysine (FDLH) is used as the corrosion inhibitor, and combined with a strong alkaline alkaline alkaline electrolyte, the carboxyl functional groups of FDLH are adsorbed on the surface of the aluminum anode to form a protective film to inhibit corrosion.
It effectively suppresses the self-corrosion and hydrogen evolution corrosion of the aluminum anode, improves the anode utilization rate and the stability of the electrolyte, significantly reduces the corrosion rate and hydrogen evolution rate, and improves the discharge performance of the aluminum air battery.
Smart Images

Figure CN119764690A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum-air batteries, and in particular to a corrosion inhibitor and an alkaline electrolyte for aluminum-air batteries and a preparation method thereof. Background Art
[0002] Aluminum-air batteries (AABs) have emerged as a promising, high-energy-density electrochemical energy storage solution against the backdrop of global energy shortages, environmental pollution, and increasing pressure to reduce carbon emissions. AABs have an impressive volumetric capacity (8056 mA h cm for aluminum anode) and a relatively low volumetric capacity (8056 mA h cm for aluminum anode). -3 ), low cost and environmentally friendly, and has great potential in solving future energy needs, advancing electric vehicle technology and supporting large-scale energy storage applications. However, due to the high electrochemical activity of aluminum, hydrogen evolution corrosion is prone to occur during battery operation, posing a safety hazard. To solve this problem, researchers have proposed various solutions to reduce corrosion and improve battery performance. Among them, alloying the aluminum anode and adding corrosion inhibitors to the electrolyte are two common methods.
[0003] The application of corrosion inhibitors in the field of aluminum-air batteries has a history of more than half a century. Many substances have been identified as effective corrosion inhibitors for aluminum anodes, including metal oxides, inorganic salts, rare earth ions, and certain organic compounds with heteroatoms or hydrophobic groups, such as carboxylic acids and surfactants. These substances generally form a protective barrier on the surface of aluminum anodes by deposition or adsorption, showing an inhibitory effect on corrosion.
[0004] As the industry's requirements for environmental protection continue to increase, the selection of green and environmentally friendly substances to replace traditional corrosion inhibitors has become an important research field. Amino acids and their derivatives have shown great potential as corrosion inhibitors because they have good biocompatibility and have multiple active groups (such as amino and carboxyl groups) in their molecular structures, which can effectively interact with metal surfaces to prevent corrosion. Summary of the invention
[0005] Based on this, the present invention provides a corrosion inhibitor and an alkaline electrolyte for an aluminum-air battery and a preparation method thereof, so as to solve the technical problems of hydrogen evolution corrosion at the anode of the aluminum-air battery and reduced Coulomb efficiency, resulting in low anode utilization and fast corrosion rate under existing technical conditions.
[0006] In order to solve the above technical problems, one of the objectives of the present invention is to provide a corrosion inhibitor for aluminum-air batteries, wherein the corrosion inhibitor is N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH).
[0007] Preferably, in the alkaline electrolyte, the concentration of N-alpha-Fmoc-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) is 1-7 mM.
[0008] Based on the same inventive concept, the present invention also provides an alkaline electrolyte for aluminum-air batteries containing the above-mentioned corrosion inhibitor, wherein the alkaline electrolyte is a deionized water solution of a strong base and N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH), and the concentration of the strong base deionized water solution is 3-5M.
[0009] Preferably, the strong base is one or both of sodium hydroxide and potassium hydroxide.
[0010] The present invention also provides a method for preparing an alkaline electrolyte for an aluminum-air battery, comprising the following steps: S1: Add N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) into deionized water, stir magnetically at 30°C until uniformly dispersed, and then cool to room temperature; S2: Dissolve a strong base in deionized water, cool to room temperature, use a rubber-tipped dropper to absorb the strong base solution, and drip it drop by drop into the N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) solution prepared in S1 to obtain an alkaline electrolyte for aluminum-air batteries.
[0011] The mechanism of action of the electrolyte is as follows: in the primary cell reaction, the carboxyl functional group of N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) is preferentially adsorbed on the surface of the aluminum anode and produces a protective film, preventing water molecules from directly contacting the surface of the aluminum anode. The self-corrosion reaction and hydrogen evolution reaction on the surface of the aluminum anode are inhibited, which significantly enhances the discharge performance and anode utilization.
[0012] The above one or more technical solutions of the present invention have the following technical effects: (1) In the present invention, FDLH is used as a corrosion inhibitor, which broadens the electrochemical stability window of the electrolyte and improves the stability of the electrolyte.
[0013] (2) In the present invention, as the concentration of FDLH corrosion inhibitor increases, the corrosion rate gradually decreases. When the FDLH concentration is 7mM, i corr From 57.77 mA cm -1 Down to 28.81 mA cm -1 , the corrosion inhibition efficiency reaches 48.85%; (3) In the present invention, as the concentration of FDLH corrosion inhibitor increases, the polarization resistance increases. When the FDLH concentration is 7 mM, the polarization resistivity reaches a maximum of 51.44%; (4) When the electrolyte prepared by the present invention is used on the surface of aluminum anode, it can effectively inhibit self-corrosion, reduce the hydrogen evolution rate, and improve the corrosion inhibition efficiency. For example, with the increase of FDLH concentration, the hydrogen evolution rate increases from 0.70 mL min −1 cm −2 Reduced to 0.3 mL / min -1 cm -2 ; (5) When the electrolyte prepared by the present invention is used in aluminum-air batteries, it can effectively improve the discharge performance of aluminum-air batteries. For example, when FDLH corrosion inhibitor is present in the electrolyte, the capacity density can reach 2531.7 mAh g −1 , the energy density can be as high as 3058.0 Wh kg −1 The anode utilization rate was significantly increased to 85.0%, and the power density increased from 14.3 mW cm −2 Increased to 66.4 mWcm −2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0015] Figure 1 , Preparation process of alkaline electrolyte for aluminum-air battery; Figure 2 , Nyquist plots of Examples 1-4 and Comparative Examples; Figure 3 , electrochemical Bode fitting spectra of Examples 1-4 and Comparative Examples, including impedance-frequency and phase angle-frequency graphs; Figure 4 , polarization curves of Examples 1-4 and Comparative Examples; Figure 5 , electrochemical window diagrams of Examples 1-4 and Comparative Examples; Figure 6 , hydrogen evolution volume diagram of Examples 1-4 and Comparative Example; Figure 7 , hydrogen evolution rate and hydrogen evolution inhibition efficiency diagram of Examples 1-4 and Comparative Examples; Figure 8 The aluminum-air battery assembled from Example 4 and the comparative example was subjected to a current density of 20 mA cm -2 The constant current discharge curve diagram below; Fig. 9, polarization curves and power density curves of the aluminum-air batteries assembled in Example 4 and the comparative example; Fig.10 , the cycle discharge curves of the aluminum-air batteries assembled from Example 4 and the comparative example; Fig.11 , voltage curves of the aluminum-air batteries assembled in Example 4 and the comparative example at different current densities; Fig.12 , SEM image of aluminum metal immersed in the solution prepared in the comparative example for 1 h; Fig.13 , SEM image of aluminum metal immersed in the solution prepared in Example 4 for 1 h; Fig.14 , AFM image of aluminum metal immersed in the solution prepared in the comparative example for 1 h; Fig.15 , AFM image of aluminum metal immersed in the solution prepared in Example 4 for 1 h; Fig.16 , the contact angle diagram obtained when the metal aluminum is immersed in the solution prepared in the comparative example for 1 h; Fig.17 , contact angle diagram obtained when metallic aluminum is immersed in the solution prepared in Example 4 for 1 h. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0017] Throughout the specification, unless otherwise specified, the terms used herein should be understood as having the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. If there is a conflict, the present specification takes precedence. The preparation process of the electrolyte prepared by the present invention is as follows Figure 1 shown.
[0018] In the following examples and comparative examples, in the effect of FDLH corrosion inhibitor on the discharge performance of aluminum-air batteries, the aluminum anodes are all commercial aluminum and the cathodes are commercial air cathodes. The air cathode is composed of a waterproof and breathable membrane, a current collecting layer and Bi2O3 - In the effect of FDLH corrosion inhibitor concentration on the corrosion of aluminum anode, a three-electrode system was used. Aluminum and copper conductors were welded as working electrodes (WE) and sealed with epoxy resin adhesive. The reaction area was 1 cm 2The counter electrode is a platinum electrode, and the reference electrode is a Hg / HgO electrode. In the electrochemical window test, the working electrode and the counter electrode are both platinum electrodes, and the reference electrode is a Hg / HgO electrode.
[0019] The aluminum anodes in the embodiments of the present invention and the comparative examples need to be pretreated before use, and the pretreatment steps include: polishing the commercial anodes with sandpaper, and the order of sandpaper used is 400 mesh, 800 mesh, 1000 mesh, and 2000 mesh, followed by ultrasonic cleaning with deionized water and anhydrous ethanol, and finally drying to ensure that the surface of the aluminum anode is smooth and flat.
[0020] Example 1 A method for preparing an alkaline electrolyte for an aluminum-air battery comprises the following steps: S1: Add 0.0469 g of N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) into 50 mL of deionized water, heat at 30°C, stir magnetically until the mixture is evenly dispersed, and then cool to room temperature; S2: Dissolve 16 g of sodium hydroxide in deionized water, cool to room temperature, and dilute to a 50 mL volumetric flask. Use a rubber-tipped dropper to draw up the sodium hydroxide solution, and drip it dropwise into the N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) solution prepared in S1 to obtain an alkaline electrolyte for aluminum-air batteries with a FDLH corrosion inhibitor concentration of 1 mM.
[0021] Example 2 A method for preparing an alkaline electrolyte for an aluminum-air battery comprises the following steps: S1: Add 0.1406 g of N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) into 50 mL of deionized water, heat at 30°C, stir magnetically until the mixture is evenly dispersed, and then cool to room temperature; S2: Dissolve 16 g of sodium hydroxide in deionized water, cool to room temperature, and dilute to a 50 mL volumetric flask. Use a rubber-tipped dropper to draw up the sodium hydroxide solution, and drip it dropwise into the N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) solution prepared in S1 to obtain an alkaline electrolyte for aluminum-air batteries with a FDLH corrosion inhibitor concentration of 3 mM.
[0022] Example 3 A method for preparing an alkaline electrolyte for an aluminum-air battery comprises the following steps: S1: Add 0.2343 g of N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) into 50 mL of deionized water, heat at 30°C, stir magnetically until the mixture is evenly dispersed, and then cool to room temperature; S2: Dissolve 16 g of sodium hydroxide in deionized water, cool to room temperature, and dilute to a 50 mL volumetric flask. Use a rubber-tipped dropper to draw up the sodium hydroxide solution, and drip it dropwise into the N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) solution prepared in S1 to obtain an alkaline electrolyte for aluminum-air batteries with a FDLH corrosion inhibitor concentration of 5 mM.
[0023] Example 4 A method for preparing an alkaline electrolyte for an aluminum-air battery comprises the following steps: S1: Add 0.3280 g of N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) into 50 mL of deionized water, stir magnetically at 30 °C until the mixture is evenly dispersed, and then cool to room temperature; S2: Dissolve 16 g of sodium hydroxide in deionized water, cool to room temperature, and dilute to a 50 mL volumetric flask. Use a rubber-tipped dropper to draw up the sodium hydroxide solution, and drip it dropwise into the N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine (FDLH) solution prepared in S1 to obtain an alkaline electrolyte for aluminum-air batteries with a FDLH corrosion inhibitor concentration of 7 mM.
[0024] Comparative Example Weigh 16 g of NaOH, dissolve it in deionized water, cool to room temperature, and dilute to volume in a 100 mL volumetric flask to obtain 100 mL, 4 mol / L sodium hydroxide solution.
[0025] In order to further verify the effect of the electrolyte prepared by the present invention on the self-corrosion performance and discharge performance of the aluminum anode, test examples 1-4 were subjected to electrochemical tests, hydrogen evolution tests, discharge performance tests and other related tests. And compared with the comparative examples, the specific test examples are as follows:
[0026] Test Example 1 Electrochemical tests were performed on the electrolytes prepared in Examples 1-4 and Comparative Examples to measure open circuit potential (OCP), electrochemical impedance spectroscopy (EIS), polarization curve (PDP) and electrochemical window. The specific test results are shown in Tables 1-2 and Figure 2-5 shown.
[0027] Table 1 Fitting results of impedance spectra of aluminum electrodes in Examples 1-4 and Comparative Examples
[0028] Table 2 Tafel curve data results of aluminum electrodes in Examples 1-4 and Comparative Examples
[0029] like Figure 2-4 It can be shown that with the increase of FDLH concentration, the polarization resistance increases and the corrosion current decreases. Figure 2-3 The electrochemical behavior of the aluminum anode was further analyzed. Figure 2 As shown in Figure 1, the Nyquist plot shows the capacitive loops in the high-frequency and low-frequency regions, and the inductive loop in the mid-frequency region. The Nyquist plots of FDLH inhibitors at different concentrations show a high degree of similarity, proving that FDLH inhibitors do not change the corrosion mechanism. Figure 3 As shown in the Bode diagram, double time constants in the high-frequency and low-frequency regions can be observed. After adding FDLH corrosion inhibitor, the increase in low-frequency impedance modulus |Z| and capacitance loop diameter indicates that a protective barrier is formed on the electrode surface. Figure 4 It can be observed that the presence of FDLH corrosion inhibitor leads to E corr Negative shift, and E corr The maximum shift is less than 85 mV, which indicates that FDLH corrosion inhibitor is a mixed corrosion inhibitor. In addition, a current platform can be observed at the anodic branch of the PDP curve, indicating that the anodic process is controlled by the diffusion step.
[0030] As shown in Table 1-2, Example 4 is the best choice. From the data in Table 1, it can be seen that R ct As the concentration of FDLH increases, the charge transfer rate decreases. This is because the FDLH corrosion inhibitor can be adsorbed on the surface of the aluminum anode, replacing the adsorption position of H2O, and the hydrogen evolution corrosion process can be delayed. After adding 7 mM FDLH corrosion inhibitor, R T Up to 0.29 Ω cm 2 , the best protection efficiency reached 51.44%. The EIS results are closely related to the PDP results. From the data in Table 2, it can be seen that after adding 7 mM FDLH corrosion inhibitor, i corr From 57.77 mA cm -1 Reduced to 28.81 mA cm -1 , the highest corrosion inhibition efficiency reached 48.85%, indicating that FDLH corrosion inhibitor can prevent the corrosion of aluminum electrode in alkaline electrolyte.
[0031] like Figure 5It can be shown that the addition of FDLH corrosion inhibitor promotes the expansion of the electrochemical window and improves the stability of the electrolyte. It is also observed that the cathode current density decreases. After adding 7mM FDLH, the current density decreases by 98.6 mA cm −1 . This further confirmed that the hydrogen evolution corrosion process was inhibited.
[0032] Test Example 2 The electrolytes prepared in Examples 1-4 and Comparative Example were subjected to hydrogen evolution tests, and the hydrogen evolution rate was determined by the water displacement method. The aluminum sample was immersed in the electrolyte for 30 minutes, and the amount of liquid discharged was recorded every 5 minutes. Figure 6 As shown in the figure: In the presence of FDLH corrosion inhibitor, the precipitation volume of H2 is significantly reduced. Figure 7 As shown in the figure: With the increase of FDLH concentration, the hydrogen evolution rate decreases and the inhibition efficiency of hydrogen evolution can reach 57.1%.
[0033] Test Example 3 To verify the effect of electrolyte on the discharge performance of aluminum-air battery, 100 mL of electrolyte prepared in Example 4 and the comparative example was placed in a plastic washing bottle, connected to the full battery device, and a circulation pump was connected to the battery to circulate the electrolyte at a rate of 5 mL / min. -2 The cyclic discharge curve is measured at a current density of 20 mA cm -2 The discharge was performed under open circuit conditions for 1 h and under open circuit conditions for 20 min, for a total of five cycles. -2 The step discharge curve under the condition of linear sweep voltammetry (LSV, 5 mV S -1 ) to generate the polarization curve of the battery.
[0034] like Figure 8-9 As shown in Figure 4, after adding FDLH corrosion inhibitor, the battery discharge voltage is more stable and the capacity density is significantly improved. This may be due to the suppression of H2 precipitation sites, which makes the distribution of discharge sites more uniform. The capacity density of metal aluminum in Example 4 reaches 2531.7 mAh g −1 , the energy density reaches 3058.0 Wh kg −1 The anode utilization rate reached 85.0%, which was significantly improved compared with the control group. After adding FDLH, the power density increased from 14.3 mW cm −2 Increased to 66.4 mW cm −2 . Fig.10 Interval discharge test was used to simulate the actual working state of the battery. The results showed that the battery containing FDLH showed a higher and more stable discharge voltage. Fig.11 A multi-step discharge test was performed, starting from 1 mA cm −2 Initially, the test lasted for 600 s. When the current density was gradually increased to 10, 20, 40, 60, 80, 100, and 120 mA cm −2 When the discharge voltage of the aluminum-air battery containing FDLH corrosion inhibitor decreases less than that of the comparative example, the voltage remains stable during each discharge time.
[0035] Test Example 4 In order to verify the corrosion degree of the metal aluminum electrode, the metal aluminum electrodes prepared in the comparative example and Example 4 were soaked in the electrolyte for 1 h, and the surface morphology of the metal aluminum was observed using SEM and AFM, and the water contact angle of the sample surface was analyzed using a contact angle tester. Fig.12 and Fig.13 As shown in the figure: in the solution prepared in Example 4, the corrosion cracks of the aluminum sample after immersion are small, indicating that the FDLH corrosion inhibitor can be adsorbed on the aluminum surface, preventing the aluminum surface from contacting with water and playing a protective role. Fig.14 and Fig.15 As shown: the aluminum sample immersed in the comparative electrolyte has a higher roughness, indicating that in the electrolyte without FDLH, the strong alkaline solution seriously corrodes the metal aluminum. After adding the FDLH corrosion inhibitor, that is, in the electrolyte prepared in Example 4, the surface becomes relatively smooth, and the roughness is reduced to 188.1 nm, indicating that under this system, the corrosion degree of the aluminum anode is reduced, and the aluminum anode is effectively protected. Figure 16-17 As shown: In the presence of FDLH corrosion inhibitor, the maximum water contact angle is 67.0°, indicating that the adsorption of FDLH corrosion inhibitor can hinder the contact between water molecules and the metal surface, increase the hydrophobicity of the aluminum surface, and inhibit the hydrogen evolution reaction.
[0036] In summary, the electrolyte prepared by the present invention solves the technical problems of low anode utilization and fast corrosion rate caused by self-corrosion and hydrogen evolution corrosion of aluminum-air battery anode under existing technical conditions. The electrochemical stability window of the electrolyte is broadened, the stability of the electrolyte is improved, the corrosion rate is gradually reduced, and self-corrosion can be effectively inhibited. At the same time, the hydrogen evolution rate is reduced, the corrosion inhibition efficiency is improved, and the discharge performance of the aluminum-air battery can be effectively improved.
Claims
1. A corrosion inhibitor for aluminum-air batteries, characterized in that: The corrosion inhibitor is N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine.
2. The corrosion inhibitor for aluminum-air battery according to claim 1, characterized in that: In an alkaline electrolyte, the concentration of the N-alpha-Fmoc-N-epsilon-tert-butyloxycarbonyl-D-lysine is 1-7 mM.
3. An alkaline electrolyte for aluminum-air batteries containing the corrosion inhibitor according to any one of claims 1 to 2, characterized in that: The alkaline electrolyte is a deionized water solution of a strong base and N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine, and the concentration of the strong base deionized water solution is 3-5M.
4. The alkaline electrolyte for aluminum-air battery according to claim 3, characterized in that: The strong base is one or both of sodium hydroxide and potassium hydroxide.
5. A method for preparing an alkaline electrolyte for an aluminum-air battery as claimed in claim 3, characterized in that: The steps include: S1: Add N-alpha-Fmoc-N-epsilon-tert-butyloxycarbonyl-D-lysine to deionized water, stir magnetically until uniformly dispersed at 30°C, and then cool to room temperature; S2: Dissolve a strong base in deionized water, cool to room temperature, use a rubber-tipped dropper to absorb the strong base solution, and drip it drop by drop into the N-alpha-fluorenylmethoxycarbonyl-N-epsilon-tert-butyloxycarbonyl-D-lysine solution prepared in S1 to obtain an alkaline electrolyte for aluminum-air batteries.